Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1073/pnas.2202661119
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the S. aureus agr quorum sensing pathway reveals a direct role for the integral membrane protease MroQ in pheromone biosynthesis

Abstract: In Staphylococcus aureus, virulence is under the control of a quorum sensing (QS) circuit encoded in the accessory gene regulator ( agr ) genomic locus. Key to this pathogenic behavior is the production and signaling activity of a secreted pheromone, the autoinducing peptide (AIP), generated following the ribosomal synthesis and posttranslational modification of a precursor polypeptide, AgrD, through two discrete cleavage steps. The integral membrane protease Agr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Four different subgroups of Agr exist with considerable differences in the amino acid sequence of, and to some extent, length of the mature autoinducing peptide (AIP) [ 21 ]. The AIP can be a hepta- to nonapeptide which is exported likely also by AgrB and trimmed at the N-terminus with the help of the non-Agr-encoded membrane-located protease MroQ, at least for the AIPs of groups 1, 2, and likely 4, while the proteolytic maturation of the product of the AgrB thiolactone-introducing step remains unknown for subgroup 3 [ 24 , 25 ]. The AIP activates the AgrC-AgrA two-component system by binding to the membrane histidine kinase AgrC, which in turn phosphorylates AgrA, a DNA-binding response regulator that when phosphorylated binds to and activates the promoters driving transcription of agrBDCA and RNAIII [ 18 ].…”
Section: Quorum Sensing In Staphylococcus Aureus :...mentioning
confidence: 99%
“…Four different subgroups of Agr exist with considerable differences in the amino acid sequence of, and to some extent, length of the mature autoinducing peptide (AIP) [ 21 ]. The AIP can be a hepta- to nonapeptide which is exported likely also by AgrB and trimmed at the N-terminus with the help of the non-Agr-encoded membrane-located protease MroQ, at least for the AIPs of groups 1, 2, and likely 4, while the proteolytic maturation of the product of the AgrB thiolactone-introducing step remains unknown for subgroup 3 [ 24 , 25 ]. The AIP activates the AgrC-AgrA two-component system by binding to the membrane histidine kinase AgrC, which in turn phosphorylates AgrA, a DNA-binding response regulator that when phosphorylated binds to and activates the promoters driving transcription of agrBDCA and RNAIII [ 18 ].…”
Section: Quorum Sensing In Staphylococcus Aureus :...mentioning
confidence: 99%
“…The necessity of MroQ in AIP production was demonstrated via generation of an mroQ knockout; deletion of the protease eliminated or severely reduced group I and II AIP production, which was restored with mroQ complementation. 156 In vitro studies further showed that substrate specificity of MroQ is dependent on the linker peptide connecting the N-terminal αhelix and the C-terminal thiolactone of its substrate; AIPs containing the helix and C-terminal macrocycle of one AIP group and the linker of another AIP group were efficiently processed. 156 However, whereas MroQ was shown to be active with groups I and II, and by homology group IV, AIP substrates, maturation of group III AIPs remains unresolved.…”
Section: Different Protease Family Enzymesmentioning
confidence: 99%
“…The second step of AIP biosynthesis requires cleavage of the LP by another integral membrane metalloprotease (M79) MroQ. The necessity of MroQ in AIP production was demonstrated via generation of an mroQ knockout; deletion of the protease eliminated or severely reduced group I and II AIP production, which was restored with mroQ complementation . In vitro studies further showed that substrate specificity of MroQ is dependent on the linker peptide connecting the N-terminal α-helix and the C-terminal thiolactone of its substrate; AIPs containing the helix and C-terminal macrocycle of one AIP group and the linker of another AIP group were efficiently processed .…”
Section: Two-step Proteolytic Processing By Different Protease Family...mentioning
confidence: 99%
“…Recent work implicates another membrane-associated peptidase in this process (MroQ), at least in certain S. aureus strains. , As the bacterial population grows, the extracellular AIP concentration likewise increases to eventually reach a local threshold that can activate the two-component signaling system formed by AgrC and AgrA. AgrC is a transmembrane receptor histidine kinase that, upon binding of AIP to its extracellular domain, trans -autophosphorylates its cytosolic domain and then transfers the phosphoryl group to its partner intracellular response regulator, AgrA .…”
Section: Introductionmentioning
confidence: 99%